Epidemiological Susceptibility Risk, Adaptive Management and Firm Performance. (9th June 2021) - Mertzanis, Charilaos
Abstract: This paper uses firm‐level information to analyse the impact of epidemic outbreak risk on individual firms' performance. Its impact on performance materializes mainly through consumer perception of risk and the resilience of the supply chain networks. The extent to which countries are prepared to identify and respond to these risks adequately is a critical factor. We therefore construct an index of epidemiological susceptibility risk (ESR), which we use to predict business performance around the world. The index captures the role of infrastructure, demographics, economic activity and institutional governance. It proves a significant predictor of corporate sales growth. It also fares well in explaining business performance during the Covid‐19 pandemic. The results remain robust to various sensitivity and endogeneity tests and after controlling for different non‐economic and institutional factors. The ESR captures diverse conditions, which may amplify or contain the contagion of epidemiological risk, and therefore it could potentially be a useful tool for predicting and managing epidemic outbreaks and their consequences on business sustainability.